Modelling, analysis and optimisation of supply chains by using Petri net models: the state-of-the-art. (1st November 2010) - Labadi, Karim; Chen, Haoxun
Driven by fierce global competition, reducing costs while improving customer services by effective supply chain logistics management has become one main concern of most companies. This has created needs for modelling, performance analysis and optimisation tools that can help these companies to improve their logistics networks and operations. In this paper, the advantages of Petri nets as modelling and analysis tools for logistics systems are demonstrated, the recent developments of using Petri net based approaches for modelling, performance analysis, and optimisation of supply chains are reviewed, and future research directions for this important area are explored.